Student's Perspective: Using Minimal Pairs Technique To Improve Pronunciation - Indriana Dewi Mawarni Marpaung; Sefia Alia Riska Sipayung; Yani Lubis (Universitas Maritim AMNI Semarang, 2023)
The Minimal Pairs technique is a technique for investigating the existence of phonemes (language sounds that can distinguish meaning) by comparing two or more forms of speech sounds in the same environment. The minimal pairs technique is used to practice pronunciation skills, especially on similar word sounds and makes it easier for us to distinguish phoneme sounds in English. This study aims to determine student perceptions of the use of minimal pairs technique in class. This research is qualitative research using questionnaires and interviews that ask students' perceptions about the use of minimal pairs technique in class. The results of this study indicate that most students have positive perceptions of using the minimal pairs technique in improving their pronunciation skills. Then they argue that their pronunciation skills improve after using the minimal pairs technique. So that this technique can be suggested as a learning method that will be applied in class learning to improve students' pronunciation skills.